Australian Experience of Total Pancreatectomy and Islet Auto Transplant (TPIAT) Utilizing a Remote Isolation Center. (July 2018) - Drogemuller, Chris; Radford, Toni; Russell, Chris; Chen, John; Khurana, Sanjeev; Torpy, David; Couper, Jennifer; Couper, Richard; Kos, Cameron; Bleasdale, Nicole; Thomas, Helen; Irvin, Allison; et al.
Abstract : Introduction: In 2015 we performed the first TPIAT in Australia on a 7 year old paediatric patient suffering hereditary chronic pancreatitis due to a PRSS1 mutation. We have since performed a further 4 TPIAT procedures, 2 paediatric and 2 adult recipients. All 5 TPIAT procedures were performed in Adelaide, South Australia at the Women's and Children's Hospital (paediatric patients) or the Royal Adelaide Hospital (adult patients). The islet isolation procedure was performed at a remote isolation center, St Vincent's Institute (SVI), Melbourne Victoria. SVI is a 1hr15min commercial flight from Adelaide or approximately 470 miles by road. Following isolation, the islets were infused back into each patient on the same day in Adelaide. Materials and Methods: In the first 2 patients a total pancreatectomy, splenectomy, cholecystectomy, and biliary and enteric reconstruction was performed. In patients 3-5 the spleen was spared during the total pancreatectomy. Once removed, the pancreas was placed in preservation solution and escorted from Adelaide to Melbourne by commercial airline. Pancreatic digestion and islet isolation were performed using Serva enzyme and standard protocols. Islet infusion into the liver was performed by cannulation of the portal vein with concomitant portal vein pressure monitoring. Results: The cold ischaemic time for all 5 pancreas was similar, ranging from 5hr to 5hr21min. The pancreas weights varied significantly, however this did not correlate with islet yield. Total IEQ ranged from 28, 254 to 653, 222 and the time from placing the islets into transplant bags through to infusion into the recipient was relatively consistent, ranging from 4-5hrs. To date, patients 1 & 3 have ceased all pre-operative pain medication and patient 4 has significantly reduced his opiate usage and is currently undergoing a controlled withdrawal and detoxification program with medical guidance to cease the remaining analgesia. Patient 5 the most recent TPIAT is in the process of weaning off her pre-operative analgesia and patient 2 suffered complications following TPIAT and is deceased. All 4 surviving patients are c-peptide positive with daily insulin requirements ranging from 10-20U and HbA1c levels of 5-8. Conclusion: We have successfully completed a pilot study involving 5 patients undergoing TPIAT for the management of chronic pancreatitis. All 5 isolations were performed at a facility remote to the hospital where the total pancreatectomy and subsequent islet infusion was performed. All surviving recipients have experienced a reduction or complete resolution of their chronic pain following TPIAT with two patients no longer requiring any form of analgesia. They are all c-peptide positive, requiring minimal doses of exogenous insulin with excellent management of their diabetes. Recently, we secured additional funding to perform 6 more TPIATs with the long-term goal of establishing TPIAT as a government funded procedure for the treatment of chronic pancreatitis. The Hospital Research Foundation South Australia. MedVet Sciences South Australia. Women's and Children's Hospital.